Ludwig van Beethoven (1770-1827): the piano concertos - Beethoven, Ludwig van 1770-1827; Bernstein, Leonard 1918-1990; Zimerman, Krystian; Wiener Philharmoniker (Hamburg Deutsche Grammophon, 2007)
"I offer this cycle to all music-loving ears as a testament of faith and of my most profound reactions to this greatest of all composers" - Leonard Bernstein (1980)"Bernstein's ability to communicate his intense feelings about Beethoven's music to the Vienna Philharmonic orchestra, and thus to the audience, is manifest not only in the energetic sweep of each performance, but also in a hundred tiny felicities ... Each interpreatation has a lived-through quality that lends it astonishing conviction." - Gramophone